A Clustering Method Approach for Portfolio Optimization - Fadilah, Iwan; Witiastuti, Rini Setyo (Management Analysis Journal, 2018)
This study aims to test the formation of the optimum portfolio using the cluster method. The data used are of financial statements and stock prices of the companies listed on the LQ-45. index The results of this research show that the cluster method can be used to form the optimal portfolio. This is because using the cluster method; the research samples were divided into three clusters that are united to the same characteristics of each company. Further research can be added the research indicators and research sample used in order that the results obtained are more varied.